VOICE DALAM BAHASA INGGRIS DAN BAHASA MONGONDOW ( SUATU ANALISIS KONTRASTIF ) - PAPUTUNGAN, DONNA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ This research entitled â€˜Voice in English and Mongondow Language:(A contrastive analysis)â€. The aims of this research are identify, to clasify, to analyze and also to contrast, the voice in English and Mongondow Language.This research used a descriptive method. The English data were collected from books and website, while Mongondow languge data were collected from several native speakers who live in Tutuyan, Bolaang Mongondow distirct. The writter used Aarts & Aartsâ€™s theory (1982) in analyzing the data and Ladoâ€™s theory (1957) in contrasting both languages to find out their differences.The data in English form consist of modal auxiliary verb, primary auxiliary verb, indirect object, direct object and to be. In Mongondow language consist of indirect and direct object.The result of this research shows that English and Mongondow language have differences in form of voice. Form of active and passive voice in English consist of to be, modal auxiliary verb, primary auxiliary verb, direct object and indirect object. While active and passive voice in Mongondow language only has direct and indirect object. There are 66 active and 66 passive voice in English.Then there are 33 active and passive voice in MongondowÂ Â Â ——————————-Keywords : Voice, English, Mongondow